Effects of Coronavirus on Nepalese Economy - Dhungel, Bashu Dev; Lamichhane, Kul Prasad (Economic Review of Nepal, 2020)
This article, Effects of Coronavirus on Nepalese Economy, focuses on the effects the coronavirus had on the economic growth in Nepal during the pandemic situation. The main objective of this study was to explore the effects of COVID-19 on the Nepalese economy and to provide some guidance to policymakers to minimize the economic losses from COVID-19. This study employed a descriptive research design to explore the impact of COVID-19 on Nepal’s GDP growth. The results indicate that the virus was found to be hitting these sectors hardest: mining and quarrying, industrial sectors, construction sectors, hotel and restaurant sectors, transportation, communication, and storage sectors. The expected growth rate of these sectors exhibits negative scenarios; however, the estimated growth rate of fishery, electricity, gas and water, health and social work, and public administration and defense exhibits positive scenarios.